Cognitive Profile Discrepancy as a Possible Predictor of Emotion Dysregulation in a Clinical Sample of Female Adolescents with Suicidal Behavior - Flora Furente; Federica Annecchini; Emilia Matera; Sabrina Serafino; Giorgia Frigeri; Alessandra Gabellone; Lucia Margari; Maria Giuseppina Petruzzelli (European Journal of Investigation in Health, Psychology and Education)
Emotional dysregulation (ED) has not yet been defined as a clinical entity, although it plays an important role in child and adolescent psychopathology. It is a transdiagnostic construct defined as the inability to regulate the intensity and quality of emotions to produce an appropriate emotional response, to cope with excitability, mood instability, and emotional over-reactivity. The aim of this study is to assess, in a sample of female patients with internalizing disorders and suicidal behavior, the correlation between cognitive profile (assessed with Wechsler Scales) and the dimensions of emotion regulation assessed with the Difficulties in Emotion Regulation Scale (DERS). We also investigated whether a discrepancy between the General Ability Index (GAI) and the Cognitive Proficiency Index (CPI) could have predictive value for certain ED domains. Our results confirmed a statistically significant prediction of the ΔGAI-CPI for individual DERS domains and for the total (p = 0.014 for DERS-TOT, p = 0.04 for GOALS, p = 0.002 for STRATEGIES and p = 0.015 for CLARITY); furthermore, IAG and PRI correlate with worse ability to find ER strategies (p = 0.04, p = 0.010). These results suggest the importance of examining the impact of cognitive vulnerabilities on the ability to manage emotions and psychopathology in general, even with normal FSIQ/GAI.